Gene Duplication and Evolution Dynamics in the Homeologous Regions Harboring Multiple Prolamin and Resistance Gene Families in Hexaploid Wheat - Huo, Naxin; Zhang, Shengli; Zhu, Tingting; Dong, Lingli; Wang, Yi; Mohr, Toni; Hu, Tiezhu; Liu, Zhiyong; Dvorak, Jan; Luo, Ming-Cheng; Wang, Daowen; Lee, Jong-Yeol; et al. (Frontiers in Plant Science, 2018)
Improving end-use quality and disease resistance are important goals in wheat breeding. The genetic loci controlling these traits are highly complex consisting of large families of prolamin and resistance genes with members present in all three homeologous A, B, and D genomes in hexaploid bread wheat. Here, orthologous regions harboring both prolamin and resistance gene loci were reconstructed and compared to understand gene duplication and evolution in different wheat genomes. Comparison of the two orthologous D regions from the hexaploid wheat Chinese Spring and the diploid progenitor Aegilops tauschii revealed their considerable difference due to the presence of five large structural variations with sizes ranging from 100 kb to 2 Mb. As a result, 44% of the Ae. tauschii and 71% of the Chinese Spring sequences in the analyzed regions, including 79 genes, are not shared. Gene rearrangement events, including differential gene duplication and deletion in the A, B, and D regions, have resulted in considerable erosion of gene colinearity in the analyzed regions, suggesting rapid evolution of prolamin and resistance gene families after the separation of the three wheat genomes. We hypothesize that this fast evolution is attributed to the co-evolution of the two gene families dispersed within a high recombination region. The identification of a full set of prolamin genes facilitated transcriptome profiling and revealed that the A genome contributes the least to prolamin expression because of its smaller number of expressed intact genes and their low expression levels, while the B and D genomes contribute similarly.